The evolutionary history of lethal metastatic prostate cancer - Gundem, Gunes; Van Loo, Peter; Kremeyer, Barbara; Alexandrov, Ludmil B.; Tubio, Jose M. C.; Papaemmanuil, Elli; Brewer, Daniel S.; Kallio, Heini M. L.; Högnäs, Gunilla; Annala, Matti; Kivinummi, Kati; Goody, Victoria; et al. (Nature (London), 2015)
The subclonal composition of human prostate tumours and their metastases has been mapped by whole-genome sequencing, thus establishing the evolutionary trees behind the development and spread of these cancers; an important observation was that metastases could be re-seeded multiple times, and spread from one tumour to another was frequently seen. Complexity in-built in tumour metastases Gunes Gundem et al . have mapped the subclonal composition of human prostate tumours and their metastases, thus establishing the evolutionary history behind the development and spread of these cancers. Importantly, they find that metastases could be re-seeded multiple times, and spread from one site of metastasis to another was frequently seen. This work sheds new light on the origin of the vast diversity of genetic and epigenetic alterations that can be seen within tumours and between primary tumours and metastases, and illustrates the clinical challenge of cancer therapy with targeted drugs. Cancers emerge from an ongoing Darwinian evolutionary process, often leading to multiple competing subclones within a single primary tumour 1 , 2 , 3 , 4 . This evolutionary process culminates in the formation of metastases, which is the cause of 90% of cancer-related deaths 5 . However, despite its clinical importance, little is known about the principles governing the dissemination of cancer cells to distant organs. Although the hypothesis that each metastasis originates from a single tumour cell is generally supported 6 , 7 , 8 , recent studies using mouse models of cancer demonstrated the existence of polyclonal seeding from and interclonal cooperation between multiple subclones 9 , 10 . Here we sought definitive evidence for the existence of polyclonal seeding in human malignancy and to establish the clonal relationship among different metastases in the context of androgen-deprived metastatic prostate cancer. Using whole-genome sequencing, we characterized multiple metastases arising from prostate tumours in ten patients. Integrated analyses of subclonal architecture revealed the patterns of metastatic spread in unprecedented detail. Metastasis-to-metastasis spread was found to be common, either through de novo monoclonal seeding of daughter metastases or, in five cases, through the transfer of multiple tumour clones between metastatic sites. Lesions affecting tumour suppressor genes usually occur as single events, whereas mutations in genes involved in androgen receptor signalling commonly involve multiple, convergent events in different metastases. Our results elucidate in detail the complex patterns of metastatic spread and further our understanding of the development of resistance to androgen-deprivation therapy in prostate cancer.